On the border of Europe and Asia: Gobio uralensis, a new species of gudgeons (Cypriniformes, Gobionidae) from the Caspian Sea basin - Ilya S. Turbanov; Aleksey A. Bolotovskiy; Oleg N. Artaev; Aleksandr A. Gandlin; Marina A. Levina; Ekaterina D. Vasil’eva; Boris A. Levin (Zoosystematics and Evolution)
A new species of cypriniform fish was discovered during studies of the riverine fish fauna of the Caspian Sea basin, employing an integrative taxonomy approach. The Ural gudgeon is herein described as a new species from the Ural River system, which is considered a geographical boundary between Europe and Asia. The new species is distinguished from the other gudgeon species by a combination of morphological characters and genetic data. Morphologically, it is very similar to Gobio volgensis from the Volga basin. Genetically, however, it is closer to G. acutipinnatus, which occurs in the upper Irtysh River (Ob’ River system), and to G. multipunctatus from the Lake Alakol basin in Central Asia (p-distance = 0.037; COI mtDNA). Therefore, the Ural gudgeon, which is endemic to the Ural River system, is of Asian rather than European origin. The biogeography of freshwater aquatic animals in the region is discussed in relation to paleogeographic events and connections between the Caspian Sea and Ob’ drainages.